Boundaries of the Human: Identities, Ontologies and Transformations in Old Norse Literature - Kreager, Adele (University of Cambridge, 2023)
This dissertation examines the definition of the human in vernacular texts preserved and transmitted in thirteenth- and fourteenth-century Iceland drawing on a variety of sources, from saga literature, mythological narrative and traditional poetics (eddic and skaldic) to legal compilations and religious works. Using three theoretical frameworks (critical posthumanism, new materialism and disability studies), I analyse how different literary modes grapple with concepts of human identity, and find that the material and conceptual boundaries between humans and their nonhuman environment of plants, landscapes, animals and objects become key sites of negotiation in constructions of the embodied self. I explore how narrators and poets offer audiences diverse visions of the human subject and body as critically embedded in, and co-constituted by, the nonhuman world—an entanglement that some texts embrace, and others reject. My research reveals the relational and contingent nature of Old Norse ontologies as expressed in literary texts, which posit identity as an evolving process rather than a fixed state. Chapter 1 investigates the productive dismemberment of male bodies in mythic narrative (*Snorra Edda*, *Poetic Edda*), alongside the fragmentation of bodies in the image-worlds of skaldic kennings and eddic riddles (*Heiðreks gátur*). I then extend this discussion by examining impaired and vulnerable bodies in *fornaldarsögur* that are supplemented by nonhuman matter, focusing on (more-than-)human embodiment in *Egils saga einhenda ok Ásmundar berserkjabana* (Chapter 2). Chapter 3 addresses human and divine perceptions of matter in mythological narrative and traditional poetics, focusing on the interconnectivity of bodies and environments, the distribution of agency and personhood across actors and objects, and the portrayal of animacy in skaldic verse and eddic riddles. Turning away from object–human relations, I next examine the ‘intimate caesura’ (Agamben) between animals and humans in the Sigurðr-cycle (*Poetic ...